Characterization of the complete plastome of medicinal plant Saururus chinensis (Saururaceae). Issue 2 (3rd July 2019) - Jin, Lei; Yang, Jin; Liu, Changkun; He, Mengling; Yan, Hanjing
Abstract: Saururus chinensis is an important medicinal plant in Southeast Asia. Here, we determined the first complete plastome of S. chinensis using high throughput Illumina sequencing technology. The S. chinensis plastome is 161, 494 bp in length and presents a typical quadripartite structure consisting of one large single-copy region (LSC, 88, 863 bp), one small single-copy region (SSC, 18, 679 bp), and a pair of inverted repeat regions (IRs, 26, 976 bp each). The phylogenetic analysis robustly supports that S. chinensis is sister to the group including the Saruma henryi, Asarum sieboldii, Piper kadsura, Piper cenocladum.